言語と、風景を形作る行為: 夏目漱石の作品における風景および環境への意識 - Agathe Tran アガタ・トラン (Projets de Paysage)
This article approaches the literary dimension of landscape action through the example of Natsume Sōseki, a major Japanese author of the beginning of the 20th century. I begin by explaining how the notion of the landscape becomes central in Meiji’s discourses and represents a cultural paradigm shift. Then, through a study of three novels by Sōseki  which focus on describing nature and space rather than following a conventional plot, I consider the landscape as an aesthetic and ideological narrative structure. I analyse how this writer enhances the landscape through a profusion of poetic and pictorial inter-cultural references and how he also de-constructs it in a post-modern fashion by modernising the homology between nature, language, and national identity. I conclude that Sôseki’s research on landscape forms has contributed to shaping a modern imaginary construct of space and identifies it as being at the inception of an environmental awareness.